2018
DOI: 10.1242/dmm.031278
|View full text |Cite
|
Sign up to set email alerts
|

Mek1 Y130C mice recapitulate aspects of the human Cardio-Facio-Cutaneous syndrome

Abstract: The RAS/MAPK signaling pathway is one of the most investigated pathways, owing to its established role in numerous cellular processes and implication in cancer. Germline mutations in genes encoding members of the RAS/MAPK pathway also cause severe developmental syndromes collectively known as RASopathies. These syndromes share overlapping characteristics, including craniofacial dysmorphology, cardiac malformations, cutaneous abnormalities and developmental delay. Cardio-facio-cutaneous syndrome (CFC) is a rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 78 publications
(98 reference statements)
0
18
0
Order By: Relevance
“…The RAS-ERK signaling pathway also regulates the expression of transcription factors, such as cell fate determinants. Numerous studies demonstrated that the enhanced activity of RAS-ERK signaling induces the expression of the transcription factor OLIG2, which promotes the fate of NSCs to the glial lineage [85,90,108]. Furthermore, the activation of RAS-ERK signaling promotes the expression of the pro-neural gene Achaete scute-like 1 (Ascl1) but blocks pro-neural gene Neurogenin 2 (Neurog2) expression.…”
Section: Ras-erk Signaling and Nervous System Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The RAS-ERK signaling pathway also regulates the expression of transcription factors, such as cell fate determinants. Numerous studies demonstrated that the enhanced activity of RAS-ERK signaling induces the expression of the transcription factor OLIG2, which promotes the fate of NSCs to the glial lineage [85,90,108]. Furthermore, the activation of RAS-ERK signaling promotes the expression of the pro-neural gene Achaete scute-like 1 (Ascl1) but blocks pro-neural gene Neurogenin 2 (Neurog2) expression.…”
Section: Ras-erk Signaling and Nervous System Developmentmentioning
confidence: 99%
“…Raf1 heterozygous knockout Small granule cell volume, increased cell death, reduced neuronal maturation [105] Postnatal lethality, growth retardation, apoptosis in the lung and liver, limbs coordination problems [106] Raf1 L613V heterozygous knock-in Increased density of astrocytes, enhanced OPCs density [107] Enhanced learning and memory [107] Mek1/2 Mek1 Y130C homozygous knock-in Increased astrocyte density, increased number of cortical oligodendrocytes [108] Pulmonary artery stenosis, cranial dysmorphia [108] Nestin-dependent Mek1/2 ablation Decrease of astrocyte precursors and OPCs, failure of gliogenesis [109] Early postnatal lethality [109] hGFAP-dependent Mek1/2 ablation Suppressed generation of astrocyte precursors and OPCs, failure of gliogenesis [109] Postnatal lethality [109] hGFAP-dependent Mek1 S218E,S222E Increase in astrocyte precursors and mature astrocytes, reduction of neuron number [109] Not described…”
Section: Raf1mentioning
confidence: 99%
See 2 more Smart Citations
“…Coordinated interactions between multiple cell types are necessary for normal brain function, but deficits in select cellular subtypes often mediate specific neurodevelopmental phenotypes. Past work has shown that ERK/MAPK signaling regulates the development of dorsal cortex-derived glutamatergic cortical projection neurons (PNs) and glia (Aoidi et al, 2018; Ehrman et al, 2014; Ishii et al, 2013; Li et al, 2012). Upstream regulators, such as Syngap1 , are also crucial for the early development of cortical glutamatergic neuron structure, excitability, and cognition (Clement et al, 2012; Ozkan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%